Advanced Materials and Structures for Extreme Operating Conditions - Skrzypek, Jacek J.; Ganczarski, Artur W.; Rustichelli, Franco; Egner, Halina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
The present monograph deals with new advanced materials, including composites, functionally graded materials, materials for high temperature service, advanced approaches to local and non-local analysis of localized damage, new description of crack deactivation, and many more. It contains the following subjects: Survey of material properties for high temperature and other extreme conditions Thermodynamics of constitutive modelling of advanced materials Developing and implementing selected constitutive models for thermo-elasto-plastic-damage materials Developing and implementing constitutive models for the specific functionally graded materials, with special attention paid to thermal barrier coatings Methodology of experimental microstructure analysis and residual stress determination with application to several materials and components includig functionally graded materials.
Material Properties for High Temperature Applications -- Thermodynamics of Constitutive Modelling of Damaged Materials -- Developing and Implementing Selected Constitutive Models for Elasto-Plastic-Damage Materials -- Developing and Implementing Constitutive Models for Specific FGM Applications -- Microstructural Analysis and Residual Stress Determination based on Scattering of Neutrons and X-ray Synchrotron Radiation.
Keywords: Mechanics; Mechanics, Applied; Materials science; Solid Mechanics; Classical Mechanics; Characterization and Evaluation of Materials